Assessment and testing of seismic hazard for planned mining sequences - Malovichko, D.A. (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
An approach to assess seismic and ground motion hazard associated with scenario(s) of future mining is suggested. The key element of the approach is the modelling of expected seismicity using the Salamon–Linkov method (Malovichko & Basson 2014) and combining the catalogues of modelled and observed seismic events. The modelling domain is discretised and it is assumed that the potency frequency distribution in each grid point can be described by the Upper Truncated model. The upper cutoff potency Pmax and slope β are presumed the same for all grid points. Pmax is estimated from the combined (observed and modelled) seismic catalogue using record theory (Section 3.4 of Mendecki 2016) and the slope β is evaluated from observed data. The parameter α of the Upper Truncated model is inferred from cumulative potency, which is calculated for each grid point using the combined catalogue of events. The probabilities of occurrence of events exceeding a specific potency are derived for each grid point, assuming that the temporal occurrence of events follows a Poisson distribution. The assessment of ground motion hazard is based on Monte Carlo simulation of ground motion accounting for uncertainties in the Ground Motion Prediction Equation and variation of expected seismicity according to the described above estimate of seismic hazard. There are two utilities of assessment of seismic and ground motion hazard in mines. Firstly, the calculated probabilities can be categorised in terms of the hazard likelihoods specified in the risk assessment matrix established at the mine. This can guide a geotechnical engineer in the required actions. Secondly, the evaluated seismic and ground motion hazard can be rigorously tested after the period of forecast is expired and the actual seismic response to planned mining is recorded. The testing procedures established in crustal seismology can be adopted. The poor performance of the forecast needs to be explained in geomechanical terms and corresponding settings of the modelling of seismicity have to be updated. The suggested approach of forecasting the seismic and ground motion hazard, as well as retrospective testing of the seismic hazard, are illustrated using planned mining sequence and seismic data from Renison mine, Australia.